2016
DOI: 10.1186/s12974-016-0560-4
|View full text |Cite
|
Sign up to set email alerts
|

Sildenafil, a cyclic GMP phosphodiesterase inhibitor, induces microglial modulation after focal ischemia in the neonatal mouse brain

Abstract: Background: Perinatal ischemic stroke is the most frequent form of cerebral infarction in neonates; however, evidence-based treatments are currently lacking. We have previously demonstrated a beneficial effect of sildenafil citrate, a PDE-5 inhibitor, on stroke lesion size in neonatal rat pups. The present study investigated the effects of sildenafil in a neonatal mouse stroke model on (1) hemodynamic changes and (2) regulation of astrocyte/microgliamediated neuroinflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(50 citation statements)
references
References 35 publications
2
48
0
Order By: Relevance
“…Data suggest that by 2-6 h after HI insult blood flow was restored to near normal in all brain regions of neonatal mice [22] . Studies using acute applications of sildenafil exhibit an influence on the distribution of brain perfusion with enhanced blood flow to the ischemic hemisphere in the neonatal rat [7] but not in neonatal [8] and adult mice [23] . Whereas lesion volumes remained unchanged after middle cerebral artery occlusion followed by PDE5 inhibition in adult mice [23,24] , the degree of tissue loss decreased after 8 days in neonatal mice injured by permanent middle cerebral artery occlusion [8] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Data suggest that by 2-6 h after HI insult blood flow was restored to near normal in all brain regions of neonatal mice [22] . Studies using acute applications of sildenafil exhibit an influence on the distribution of brain perfusion with enhanced blood flow to the ischemic hemisphere in the neonatal rat [7] but not in neonatal [8] and adult mice [23] . Whereas lesion volumes remained unchanged after middle cerebral artery occlusion followed by PDE5 inhibition in adult mice [23,24] , the degree of tissue loss decreased after 8 days in neonatal mice injured by permanent middle cerebral artery occlusion [8] .…”
Section: Discussionmentioning
confidence: 99%
“…Studies using acute applications of sildenafil exhibit an influence on the distribution of brain perfusion with enhanced blood flow to the ischemic hemisphere in the neonatal rat [7] but not in neonatal [8] and adult mice [23] . Whereas lesion volumes remained unchanged after middle cerebral artery occlusion followed by PDE5 inhibition in adult mice [23,24] , the degree of tissue loss decreased after 8 days in neonatal mice injured by permanent middle cerebral artery occlusion [8] . In our model, results revealed no improvement in histological scoring after sildenafil treatment independently of the frequency of injections, and we did not detect any hindrance of progression, apparent by an increased injury score at P47 suggesting that sildenafil does not prevent lesion enlargement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Associated with these beneficial effects, sildenafil had anti-inflammatory effects, reducing astrogliosis and GFAP-positive cell density and decreasing microglial density. A very recent study by Moretti et al [204] also demonstrated that sildenafil modulates neuroinflammation in the ischemia model induced in C57BL/6 mice P9 pups by permanent middle cerebral artery occlusion. Animals were treated with a single dose of sildenafil (Viagra ® , Pfizer, 10 mg/kg i.p., given 5 min after artery occlusion), which provided a reduction of the mean lesion 8 days after ischemia; also, it reduced the number of GFAP-positive cells, decreased microglial density, and modulated the M1 and M2 profiles of microglia/macrophages in the late phase after ischemia.…”
Section: Strokementioning
confidence: 90%